2012
DOI: 10.1016/j.breast.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging sensitivity of dedicated positron emission mammography in relation to tumor size

Abstract: Positron emission mammography (PEM) has been reported to have higher sensitivity than whole-body positron emission tomography (PET)due to higher spatial resolution. However, no direct evidence exists regarding the imaging sensitivity of PEM related to lesion size. In the present study, imaging sensitivity of PEM was investigated in relation to pathologically confirmed tumor size. A total of 113 breast lesions from 101 patients were included in the analysis. The patients underwent (18)F-fluorodeoxyglucose (FDG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 14 publications
0
41
0
1
Order By: Relevance
“…Meta-analyses of the accuracy of whole-body 18 F-FDG PET used after standard diagnostic workup for patients with suspected breast lesions demonstrated sensitivities of 83%-89% and specificities of 74%-80% (3,4). For patients with newly diagnosed biopsyproven breast cancer, the sensitivity of combined PET/CT was 87% (5,6). However, sensitivity is less than 50% for small (#1 cm), low-grade invasive cancers and ductal carcinoma in situ (DCIS).…”
Section: Types Of Molecular Imaging Used For Breast Cancermentioning
confidence: 99%
“…Meta-analyses of the accuracy of whole-body 18 F-FDG PET used after standard diagnostic workup for patients with suspected breast lesions demonstrated sensitivities of 83%-89% and specificities of 74%-80% (3,4). For patients with newly diagnosed biopsyproven breast cancer, the sensitivity of combined PET/CT was 87% (5,6). However, sensitivity is less than 50% for small (#1 cm), low-grade invasive cancers and ductal carcinoma in situ (DCIS).…”
Section: Types Of Molecular Imaging Used For Breast Cancermentioning
confidence: 99%
“…With dedicated configurations, the recent PEM system has high spatial resolution, up to 2.4 mm. In the prospective study from Eo et al [45], the imaging sensitivity of PEM was compared with that of PET/CT in relation to tumor size. The results showed that PEM had significantly higher sensitivity in small-sized tumours <2 cm than PET/CT.…”
Section: Pemmentioning
confidence: 99%
“…7 Preoperative evaluation has been one of the primary proposed indications for PEM technology and a number of studies have been performed to investigate the efficacy of PEM in this setting. 4,5,[126][127][128] Findings from a large multicenter trial comparing PEM to MRI in preoperative planning were recently reported by Berg et al 4,5 In preoperative evaluation of the ipsilateral breast in 388 patients, 4 the addition of either PEM or MRI to conventional imaging (mammography and/or ultrasound) improved sensitivity for additional malignancies compared to conventional imaging alone. PEM and MRI were found to be complementary: adding MRI to conventional imaging detected additional disease in 13% of patients, adding PEM to conventional imaging detected additional disease in 11% of patients, and the combination of conventional imaging with both MRI and PEM detected additional disease in 18% of patients.…”
Section: Ivb Preoperative Evaluationmentioning
confidence: 99%